1997
DOI: 10.1192/bjp.170.1.62
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the Symptoms of dementia on caregivers

Abstract: Variability in conceptual and methodological approaches and inconsistencies in the reported findings have prevented firm conclusions from being drawn. However, the literature provided support for a relationship between non-cognitive features in dementia and psychological problems in caregivers, and suggested possible associations between cognitive deficits and some negative care-giver outcomes. New methodological and conceptual approaches are required if decisive evidence is to be forthcoming. This information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
168
0
8

Year Published

1998
1998
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 257 publications
(184 citation statements)
references
References 28 publications
8
168
0
8
Order By: Relevance
“…As for the daily activities and the burden they impose on the caregiver, previous research findings are inconsistent 19,25,26 . In this study, instrumental and basic daily activities which had a greater influence on burden were: using the telephone, locomotion, going shopping, carrying out household chores, bathing and getting dressed.…”
Section: Discussionmentioning
confidence: 89%
“…As for the daily activities and the burden they impose on the caregiver, previous research findings are inconsistent 19,25,26 . In this study, instrumental and basic daily activities which had a greater influence on burden were: using the telephone, locomotion, going shopping, carrying out household chores, bathing and getting dressed.…”
Section: Discussionmentioning
confidence: 89%
“…Research also suggested that an individual's perceived quality of life is associated with the amount and types of available social support (Schultz & Martire 2004;Donaldson, Tarrier & Burns 1997).…”
Section: Distress and Quality Of Life Among Family Carers Of A Relatimentioning
confidence: 99%
“…So zeigten verschiedene Autoren, dass Angehörige, die kognitiv Beeinträchtigte pflegen, höhere Werte in verschiedenen Belastungsindikatoren (Depressions-und Angstskalen, körperliche Beschwerden, subjektive Belastung) aufweisen als Angehörige von rein körperlich Erkrankten oder Nicht-Pflegende (Clipp & George, 1993;Houlihan, 1987;Sistler, 1989). Es sind jedoch nicht so sehr die kognitiven Defizite selbst, die mit Stresserleben assoziiert sind, sondern vielmehr die Verhaltensstörungen, die aus den kognitiven Beeinträchtigungen resultieren (Bédard, Molloy, Pedlar, Lever & Stones, 1997;Coen, Swanwick, O'Boyle & Coakley, 1997;Donaldson, Tarrier & Burns, 1997;Johannsen, 1994 Aktivitäten an als Angehörige nichtaphasischer Schlaganfallbetroffener (Denman, 1998).…”
Section: Art Der Erkrankungunclassified